5
$\begingroup$

If $\triangle$ be the area of $\triangle ABC$ with side lengths $a,b,c$. Then show that $\displaystyle \triangle\leq \frac{1}{4}\sqrt{(a+b+c)\cdot abc}$

and also show that equality hold if $a=b=c$.

$\bf{My\; Try}::$ Here we have to prove $4\triangle\leq \sqrt{(a+b+c)\cdot abc}$

Using the formula $$\triangle = \sqrt{s(s-a)(s-b)(s-c)},$$ where $$2s=(a+b+c)$$

So $$4\triangle = \sqrt{2s(2s-2a)(2s-2b)(2s-2c)}=\sqrt{(a+b+c)\cdot(b+c-a)\cdot(c+a-b)\cdot(a+b-c)}$$

Now using $\bf{A.M\geq G.M}$ for $(b+c-a)\;,(c+a-b)\;,(a+b-c)>0$

$$\displaystyle \frac{(b+c-a)+(c+a-b)+(a+b-c)}{3}\geq \sqrt[3]{(b+c-a)\cdot(c+a-b)\cdot(a+b-c)}$$

So we get $\displaystyle (a+b+c)\geq 3\sqrt[3]{(b+c-a)\cdot(c+a-b)\cdot(a+b-c)}$

But I did not understand how can I prove above inequality

help Required

Thanks

$\endgroup$
  • 2
    $\begingroup$ Just a thought, a triangle with sides $s-a$, $s-b$, $s-c$, has the area $\sqrt{(a+b+c)\cdot abc}$. $\endgroup$ – Sawarnik Feb 25 '14 at 9:17
6
$\begingroup$

For a triangle

$\Delta = \frac{abc}{4R} = rs$

Now in your inequality you can put in the values to get

$R \ge 2r$

This is known to be true since the distance between incentre and circumcentre $d^2 = R(R-2r)$

Thus your inequality is proved

$\endgroup$
7
$\begingroup$

It helps to write down what you want to prove:

$$(b+c-a)(c+a-b)(a+b-c) \le abc$$

You viewed the left-hand expression as a geometric mean, but replacing it by a arithmetic mean does not work because the resulting inequality is an AM-GM inequality in the wrong direction, so you need to try something else.

There are many ways to proceed, but a good routine first step is a substitution that replaces $a, b, c$ who are linked by triangle inequalities with $2x=b+c-a$, $2y=c+a-b$, $2z=a+b-c$ who are simply positive numbers.

The desired inequality becomes:

$$8xyz \le (y+z)(x+z)(x+y).$$

But this is simply a product of three AM-GM inequalities:

$$\sqrt{yz}\sqrt{xz}\sqrt{xy}\le \frac{y+z}2\frac{x+z}2\frac{x+y}2.$$

So everything is proved.

Alternatively, if you do not see it, you can simply expand the product and apply one AM-GM inequality to the 8 terms.

$\endgroup$
4
$\begingroup$

Thanks mathlove,phira,and user for solution.

My prove for $(b+c-a)\cdot(c+a-b)\cdot(a+b-c)\leq abc$, where $a,b,c$ are the sides of a $\triangle$.

Using $\;\;\;\; \{b+(c-a)\}\cdot \{b-(c-a)\} = b^2-(c-a)^2\leq b^2$

similarly $ \{c+(a-b)\}\cdot \{c-(a-b)\} = c^2-(a-b)^2\leq c^2$

similarly $\{a+(b-c)\}\cdot \{a-(b-c)\} = a^2-(b-c)^2\leq a^2$

Multimply these three equations, we get $(b+c-a)\cdot(c+a-b)\cdot(a+b-c)\leq abc$

and equality hold when $a=b=c$

$\endgroup$
  • 1
    $\begingroup$ That is a nice proof. $\endgroup$ – Phira Dec 29 '13 at 10:56
3
$\begingroup$

We know $$S=\frac{\sqrt{(a+b+c)(-a+b+c)(a-b+c)(a+b-c)}}{4}.$$

So, all we need is to prove the following : $$(-a+b+c)(a-b+c)(a+b-c)\le abc.$$

This is a well known inequality. Proof is here.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.